Implementation of RFID Technology as an Innovative Solution for Payment Systems in Supermarkets - Adi Fajaryanto; Mohamad Vikar Dio Lopes Islami; Munaji; Rizal Arifin; Mohammad Bhanu Setyawan (oneamrd (One a Mllions Dreams Corporation), 2025)
This research focuses on the application of Radio Frequency Identification (RFID) technology as an innovative solution for the payment system at Islamic Boarding School. The current manual payment system causes several problems, such as excessively long queues, human error, and lack of parental supervision of financial transactions. The purpose of this research is to design and implement an RFID-based payment system to address these problems by increasing transaction speed, reducing errors, and improving operational efficiency. This system is designed to facilitate fast and accurate payments while minimizing human intervention. This research uses a System Development Life Cycle (SDLC) approach with a Waterfall model to ensure the system development process runs systematically and structured, from the design stage to implementation. The results show that the RFID-based payment system successfully increases transaction efficiency, reduces queues, and provides better financial monitoring for administrators and students. This system is also in line with the goal of modernizing Islamic boarding school operations, creating a more professional and enjoyable environment. This research highlights the benefits and challenges in implementing RFID technology in an academic environment, and provides recommendations for further development in the future.